Air pollution impacts on plants in East Asia - Izuta, Takeshi, 1960- (Springer, 2017)
This is the only book to offer an up-to-date overview of air pollution in East Asia and the effects of air pollutants such as ozone, acid deposition and aerosols on Asian crops and trees. It is unique in that it discusses the fundamentals of environmental plant science and research advances in the area at the plant ecophysiology level. It addresses various topics, including gaseous air pollutants such as ozone; soil acidification and atmospheric nitrogen deposition due to acid deposition; PM2.5 and the effects of air pollutants on growth, yield and physiological functions such as photosynthesis of crops and trees in East Asia. It is a valuable resource for environmental scientists, plant scientists, government officials, industrialists, environmentalists, undergraduate and graduate students and anyone interested in the application of the latest findings to agricultural production and protection of forest ecosystems in Asia. It also provides useful information for professionals involved in research, development, production, processing and marketing of agricultural products, including those in developing countries who are interested in advanced environmental science in this field.
Keywords: Plants -- Effect of air pollution on -- East Asia.; Plant ecology -- East Asia.; Air -- Pollution.; East Asia.; elektronické knihy; electronic books